Pulmonary adverse events of small molecule JAK inhibitors in autoimmune disease: systematic review and meta-analysis. (14th May 2020) - Khoo, Jun K; Barnes, Hayley; Key, Seraphina; Glaspole, Ian N; Östör, Andrew J
Abstract: Objectives: Small molecule tyrosine kinase inhibitors [smTKI, comprising mostly of Janus kinase (JAK) and to a lesser extent, spleen tyrosine kinase (SyK) inhibitors] modulate the cytokine receptor-mediated intracellular signal cascade, and are an effective treatment for autoimmune diseases and malignancies. As smTKI are novel, long-term safety is uncertain. Due to increasing use, characterization of their true adverse event profile is critical. Methods: We performed a systematic review and meta-analysis of all published trial data on the pulmonary and serious adverse effects of smTKIs in autoimmune disease. EMBASE, MEDLINE, CENTRAL and Pneumotox databases were searched up to April 2019 for randomized controlled trials, observational studies and post marketing surveillance, comparing any smTKI with placebo or another therapy, or as monotherapy at different doses. Primary outcomes comprised of any respiratory complications including upper and lower respiratory tract infections (URTI, LRTI), influenza, pneumonia, opportunistic respiratory infections, drug-induced interstitial lung disease, pulmonary embolism and lung neoplasm. Results: We identified 4667 citations for screening, and selected 319 studies for full text review. Seventy-nine studies were analysed, including 47 randomized controlled trials, 25 observational studies and seven post-marketing surveillance studies, comprising 159 652 participants. There were significantly increased risks of URTI [risk difference (RD) 0.03; 95% CI: 0.01, 0.05; P  = 0.00; 36 studies, 14 724 participants], LRTI (RD 0.01; 95% CI: 0.00, 0.02; P  = 0.02; 24 studies, 12 302 participants), influenza (RD 0.01; 95% CI: 0.00, 0.01; P  = 0.04; 22 studies, 10 684 participants), and pneumonia (RD 0.00; 95% CI: 0.00, 0.01; P  = 0.02; 33 studies, 15 511 participants). No increased risk was found for other respiratory complications, including pulmonary embolism. Conclusion: SmTKI increases the risk of non-opportunistic respiratory infections compared with placebo. The risk of any serious pulmonary adverse events is low.